What is Rural Economics - Ise, John (Quarterly Journal of Economics, 1920)
Three groups of rural economists, 300. — Dominance of the first group, emphasizing farm management, 301. — Its position unsound in principle, 302. — Difficulties of combining the individual with the social point of view, 303. — Multiplicity of subjects treated, 304. — Doubtful whether rural economics can be separated from general economics, 308.